Hubungan Antara Ketajaman Visual dan Prestasi Belajar: The Relationship Between Visual Acuity and Learning Achievement - Satrio, Joko; Novitasari, Emy (Chakra Brahmanda Lentera Institute, 2026)
Good vision is essential for students to be able to perform academically and achieve their educational goals. This paper is focused on how visual clarity affects learning improvement among ninth-grade students (14-16 years old) at an Islamic boarding school. The research focused on a quasi-experimental methodology involving a single group with a pre-test and post-test paradigm. Measuring learning achievement involves assessing standard academic test score differences pre-and post-intervention. These differences were then categorized into distinct ordinal classifications. Participants’ vision acuity was assessed using a Snellen chart and categorized into three different levels: good, moderate, and poor. Descriptive statistics were employed to analyze the data. From the study, it was concluded that visual acuity and learning achievement were unrelated (χ² = 6.34; df = 4; p = 0.1751). Descriptively, students with good visual acuity actually showed higher learning improvement compared to students with poor vision. Although the result is not statistically significant, the result shows that good vision should be in students for them to perform academically. For students to perform academically, it means supporting students with available resources. Affordable resources include routine vision test evaluation and the provision of glasses if needed.